Comparison of three different options for immediate treatment of painful temporomandibular disorders: a randomized, controlled pilot trial - Giannakopoulos, Nikolaos Nikitas; Katsikogianni, Eleni; Hellmann, Daniel; Eberhard, Lydia; Leckel, Michael; Schindler, Hans J.; Schmitter, Marc (Acta odontologica Scandinavica, 2016)
Objective: The purpose of this study was to compare the short-term effectiveness of three different types of immediate, non-pharmacological intervention for alleviation of the painful symptoms of temporomandibular disorders (TMD).Material and methods: Thirty-six patients (mean age 41.6 ± 16.7 years, 25 females) diagnosed with non-dysfunctional painful TMD received counselling and subsequently were randomly allocated to three treatment groups: patients in Group A received prefabricated oral splints with water-filled elastic pads (Aqualizer®), those in Group B were provided with vacuum-formed co-polyester oral splints and those in Group C were given appointments to receive Michigan-type hard splints. Clinical examination was conducted, at baseline and after 2 weeks, by use of the RDC/TMD. Current pain intensity was determined by evaluation of graded chronic pain status (GCPS) on a numerical rating scale (NRS). Active maximum mouth opening without pain (AMMOP) was also measured. Paired sample t-tests and one-way analysis of variance with a significance level of p ≤ 0.05 were conducted.Results: After 2 weeks, overall mean current pain was reduced by 41.95% (p < 0.001). Current pain reduction was significant for Group B (66.6%, p < 0.001) but not for Groups A (37.88%, p = 0.56) and C (22.29%, p = 0.26). After 2 weeks, current pain level for Group B was significantly lower than that for Group C (p = 0.041). Overall, there was a statistically significant increase of AMMOP (p = 0.01).Conclusion: All therapeutic options were pain-reducing. The results from this study suggest that cost-effective and time-effective intervention of counselling combined with use of a vacuum-formed splint is a favourable option for initial, short-term treatment of painful TMD.
Gesehen am 08.06.2020